The art of Miyazaki's Spirited away - Lu, Alvin; Oniki, Yuji; Evers, Izumi (Viz Communications, Inc., 2016)
Provides sketches, backgrounds, and character designs from the film "Spirited away" and includes information about the making of the film as well as the screenplay.